PREVENTION OF RhD ALLOIMMUNIZATION IN RhD NEGATIVE WOMEN - Lubusky, Marek (Biomedical papers, 2010)
Background: Despite the introduction of anti-D prophylaxis into clinical practice, RhD alloimmunization still presents a problem to date. The actual incidence of RhD alloimmunization in pregnant women remains unknown in most countries. Anti-D immunoglobulin is administered to RhD negative women at a fixed dose and in much greater amounts than is actually necessary. On the other hand, it is not possible to diagnose cases where greater doses are needed. To optimize the prevention of RhD alloimmunization in RhD negative women, it is important to diagnose conditions that lead to fetomaternal hemorrhage (FMH), precisely determine the volume and subsequently administer the appropriate dose of anti-D immunoglobulin. The possibility to accurately detect FMH and precisely determine its volume would enable more effective and less costly prevention of RhD alloimmunization. Anti-D immunoglobulin could be administered only in indicated cases and only in doses essentially necessary for prevention of RhD alloimmunization.Methods and results: The Cochrane and UpToDate databases of systematic reviews, as well as national guidelines, were reviewed.Conclusions: Due to the medical significance and indispensable economic costs associated with prevention of RhD alloimmunization, it would be appropriate to establish exact methodical guidelines. The text itself should be limited to a list of potentially sensitising events during which anti-D immunoglobulin should be administered to RhD negative women if anti-D antibodies are not already present. Following each potentially sensitising event, the minimal dose of anti-D immunoglobulin necessary for prevention of RhD alloimmunization should be determined. After 20 weeks of gestation, the volume of FMH should also be determined to specify the necessary dose of anti-D immunoglobulin.
Keywords: Anti-D immunoglobulin/RhD alloimmunization/Fetomaternal hemorrhage